Characterization and pathogenicity of extracellular serine protease MAP3292c from Mycobacterium avium subsp. paratuberculosis - Liu, Hongxiu; Dang, Guanghui; Zang, Xinxin; Cai, Zhuming; Cui, Ziyin; Song, Ningning; Liu, Siguo (Microbial pathogenesis, 2020)
Serine protease is the virulence factor of many pathogens. However, there are no prevailing data available for serine protease as a virulence factor derived from Mycobacterium avium subsp. paratuberculosis (MAP). The MAP3292c gene from MAP, the predicted serine protease, was expressed in Escherichia coli and characterized by biochemical methods. MAP3292c protein efficiently hydrolyzed casein at optimal temperature and pH of 41 °C and 9.0, respectively. Furthermore, divalent metal ions of Ca2+ significantly promoted the protease activity of MAP3292c, and MAP3292c had autocleavage activity between serine 86 and asparagine 87. Site-directed mutagenesis studies showed that the serine 238 residue had catalytic roles in MAP3292c. Furthermore, a BALB/c mouse model confirmed that MAP3292c significantly promoted the survival of Mycobacterium smegmatis in vivo; caused damage to the liver, spleen, and lung; and promoted the release of inflammatory cytokines IL-1β, IL-6, and TNF-α in mice. Finally, we confirmed that MAP3292c was relevant to mycobacterial pathogenicity. •MAP3292c protein efficiently hydrolyzed casein and had autocleavage activity.•MAP3292c serine protease promoted the survival of MS in mice and caused damage to the liver, spleen, and lung.•MAP3292c serine protease promoted the release of inflammatory cytokines in mice.